478 DIFFUSION-WEIGHTED IMAGING IMPROVES OUTCOME PREDICTION IN ADULTS WITH DIFFUSE AXONAL INJURY. (1st January 2006) - Hou, D. J.; Tong, K. A.; Ashwal, S.; Joo, E.; Shutter, L.; Obenaus, A.
Abstract : In traumatic brain injury (TBI), diffuse axonal injury (DAI) accounts for a significant portion of intra-axial injury. Past studies have shown diffusion-weighted magnetic resonance imaging (DWI) to be sensitive in detecting visible DAI lesions; however, diffuse lesions are frequently not seen on imaging. In this study, we focused on detecting nonvisible, quantifiable diffusion changes using an apparent diffusion coefficient (ADC) map. Findings were correlated to injury using admission Glasgow Coma Scale (GCS) and to long-term outcome using Glasgow Outcome Score (GOS) at 6-12 months after injury. Thirty-seven adults with TBI (mean age 32 yrs, range 18-70 yrs) were studied in addition to 35 age-matched controls. DWI was performed using single-shot echo planar technique (TR/TE = 4, 000/110 milliseconds; 5 mm thick). Twenty-eight regions of interest (ROI) were manually drawn on the corresponding ADC maps in predetermined locations and ADC values were recorded. All ROIs excluded visibly abnormal areas on the T2-weighted images. Brain regions were categorized into 5 zones: peripheral gray matter, peripheral white matter, deep gray matter, deep white matter, and posterior fossa. Admission GCS score was dichotomized into "severe" (3-8) or "mild/moderate" (9-15) injury. The GOS was dichotomized into "poor" (1-3) or "good" outcome (4-5). Statistical analysis was performed using the ANOVA method with Scheffe and Tukey HSD post hoc comparisons. In the ROIs, DWI was able to detect greater abnormalities than conventional MRI. Mean ADC values in all brain zones were significantly different between subjects and controls ( p ≤ .05). When comparing zones, the "severe" injury GCS category had significantly higher mean ADC values than the controls ( p ≤ .05). In the posterior fossa, the "severe" injury group had significantly different mean ADC values than the "mild/moderate" injury group ( p = .034). When focusing on the GOS, the "good" outcome group had significantly higher mean ADC values when compared to controls ( p ≤ .05). In the deep gray matter, the "good" and "poor" outcome groups showed a significant mean ADC difference ( p = .0001). This study concludes that ADC maps can be used to detect nonvisible DAI, which is frequently not seen, and that injuries in the deep gray matter can be used to predict outcome in adult TBI patients.